2020
DOI: 10.1021/acs.jpcc.0c00937
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Microscopic Structure of a “Water-in-Salt” Lithium Ion Battery Electrolyte Probed with Ultrafast IR Spectroscopy

Abstract: “Water-in-salt” electrolytes have been demonstrated to have potential applications in the field of high-voltage aqueous lithium ion batteries (LIBs). However, the basic understanding of the structure and dynamics of the concentrated “water-in-salt” electrolytes at the molecular level is still lacking. In this report, the structural dynamics of the concentrated lithium bis­(tri­fluoro­methane sulfonyl)­imide (LiTFSI) aqueous solutions were investigated using Fourier transform infrared (FTIR) spectroscopy and ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
43
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 68 publications
10
43
1
Order By: Relevance
“…On p 8460 of ref , the FTIR data (Figure 4a) presented are inconsistent with the previously reported results. , In the FTIR spectra of LiTFSI system, at the highest salt concentration, two peaks centered at 2430 and 2630 cm –1 can be resolved. This sounds a bit strange.…”
mentioning
confidence: 99%
“…On p 8460 of ref , the FTIR data (Figure 4a) presented are inconsistent with the previously reported results. , In the FTIR spectra of LiTFSI system, at the highest salt concentration, two peaks centered at 2430 and 2630 cm –1 can be resolved. This sounds a bit strange.…”
mentioning
confidence: 99%
“…This broadening is attributed to increased viscosity of the electrolyte [23] . The 17 O peak related to the salt only starts changing once the concentration of LiTFSI salt rises above 10 m , meaning that only at these concentrations, structure of TFSI − anions is affected by lower population of water molecules and anions start forming three‐dimensional ion networks forming heterogeneous domains [28] . Similar broadening at higher concentrations (Figure 2a) has been reported for 17 O NMR peak in mixed cation (potassium and lithium) acetate electrolytes, [23] where broadening of the peak becomes clear at concentrations of 17.8 m KOAc+4.4 m LiOAc and more.…”
Section: Structural Properties Of Ions In the Electrolytementioning
confidence: 99%
“…The high conductivities actually stem from water‐ion structures [41] . Water‐solvated Li + ions can move via bulk‐like water domains or nanometric water channels (diameter of about 1.2 nm) network formed by TFSI anions at a fast rate via vehicular‐type ion transport [28,43,44] . The type of ion transport is believed to change to more of a hopping‐type process due to lack of sufficient bulk‐like water, [15] when the concentration of the salt increases to values where the water/salt ratio gets close to 2 or lower, such as Li(TFSI) 0.7 (BETI) 0.3 ⋅ 2H 2 O hydrate melt [32] and Li 0.2 K 0.8 OAc ⋅ 1.3H 2 O [23] .…”
Section: Macroscopic (Physicochemical) Propertiesmentioning
confidence: 99%
“…Such a structure enables the preferential reduction of the anion instead of water and the formation of stable interphase, thus expanding the voltage window 30 . Moreover, it has been demonstrated that the cation transport in a concentrated electrolyte is closely associated with the structural dynamics of water molecules 31 . Despite the high viscosity, the ionic conductivity is not compromised, due to the presence of both bulk‐like and interfacial water molecules.…”
Section: Hydration Of Cationsmentioning
confidence: 99%
“…30 Moreover, it has been demonstrated that the cation transport in a concentrated electrolyte is closely associated with the structural dynamics of water molecules. 31 Despite the high viscosity, the ionic conductivity is not compromised, due to the presence of both bulk-like and interfacial water molecules. Such a feature builds an intertwined high-way of dissolved ions and nanometric bulk water channels that conducts the cation fast.…”
Section: Hydration Of Cationsmentioning
confidence: 99%